Examination of teacher’s opinions regarding normal development students and students with special needs education in the same class - Aydin, Sefket; Aydin, Ozgul; Kirikkaleli, Nurdan Ozrecberoglu; Serol, Nese (Asian Journal of Contemporary Education, 2023)
This study examines teacher opinions about the education needs of children with normal and special abilities in the same class at a Turkish Republic of Northern Cyprus (TRNC) primary school. Therefore, in order to increase the success of the students studying in the same class, the opinions and suggestions of the teachers were examined and the things to be done were stated. As one of the qualitative research methods, the descriptive survey method was used in the study. According to purposive criterion sampling, 84 primary school teachers were sampled for this study. The semi-structured interview forms were used to collect the data related to teachers’ opinions. The obtained data were analyzed by content analysis. As a result, it shows that this prepares students with special needs for socialization by introducing them to students at different developmental levels. However, when the teachers’ opinions were examined, it was stated that the education applied in this way had negative aspects. Due to the deterioration of the classroom order, it was determined that sufficient time could not be allocated to special needs students. At this point, participants emphasized the importance of designing appropriate education programs for special-needs students in order to ensure their success.